Accelerated in vitro recellularization of decellularized porcine pericardium for cardiovascular grafts. (24th February 2021) - Filova, Elena; Steinerova, Marie; Travnickova, Martina; Knitlova, Jarmila; Musilkova, Jana; Eckhardt, Adam; Hadraba, Daniel; Matejka, Roman; Prazak, Simon; Stepanovska, Jana; Kucerova, Johanka; Riedel, Tomáš; et al.
Abstract: An ideal decellularized allogenic or xenogeneic cardiovascular graft should be capable of preventing thrombus formation after implantation. The antithrombogenicity of the graft is ensured by a confluent endothelial cell layer formed on its surface. Later repopulation and remodeling of the scaffold by the patient's cells should result in the formation of living autologous tissue. In the work presented here, decellularized porcine pericardium scaffolds were modified by growing a fibrin mesh on the surface and inside the scaffolds, and by attaching heparin and human vascular endothelial growth factor (VEGF) to this mesh. Then the scaffolds were seeded with human adipose tissue-derived stem cells (ASCs). While the ASCs grew only on the surface of the decellularized pericardium, the fibrin-modified scaffolds were entirely repopulated in 28 d, and the scaffolds modified with fibrin, heparin and VEGF were already repopulated within 6 d. Label free mass spectrometry revealed fibronectin, collagens, and other extracellular matrix proteins produced by ASCs during recellularization. Thin layers of human umbilical endothelial cells were formed within 4 d after the cells were seeded on the surfaces of the scaffold, which had previously been seeded with ASCs. The results indicate that an artificial tissue prepared by in vitro recellularization and remodeling of decellularized non-autologous pericardium with autologous ASCs seems to be a promising candidate for cardiovascular grafts capable of accelerating in situ endothelialization. ASCs resemble the valve interstitial cells present in heart valves. An advantage of this approach is that ASCs can easily be collected from the patient by liposuction.